Unraveling the molecular dependence of femtosecond laser-induced thermal lens spectroscopy in fluids. Issue 3 (10th December 2019) - Singhal, Sumit; Goswami, Debabrata
Abstract : Fluid systems exhibit thermal lens effects due to laser irradiation accompanied by convection and in contrast primarily conductive heat dissipation is observed in solids. Abstract : Fluid systems exhibit thermal lens effects due to laser irradiation accompanied by convection and in contrast primarily conductive heat dissipation is observed in solids. The presence of a significant convective mode modifies the temperature gradient in fluids resulting in a deviation of the experimental results from theories that are based on pure conduction. Herein, we present a carefully designed femtosecond laser experiment that keeps the heat generation process constant in order to account for the effect of molecular properties on thermal dissipation. We derive a theoretical model that introduces and characterizes the additional convective heat transfer in thermal lens (TL) spectroscopy which explains our observed experimental results. We measured the TL signal for a series of liquid aliphatic alkanes, ranging from hexane to decane, and their comparison has proven the validity of our model. The influence of convective heat transfer on the TL signal is predicted in terms of the dimensionless Peclet number ( P E ). The lower values of P E for alkanes with longer carbon chains indicate that the convective flow of heat slows down substantially for larger molecules.